KRAS Mutant Allele Fraction in Circulating Cell-Free DNA Correlates With Clinical Stage in Pancreatic Cancer Patients - Wang, Zhe-Ying; Ding, Xiao-Qing; Zhu, Hui; Wang, Rui-Xian; Pan, Xiao-Rong; Tong, Jian-Hua (Frontiers in Oncology, 2019)
Background: The research on circulating tumor DNA (ctDNA) in pancreatic cancer (PC) has emerged recently. Although the detection rate of KRAS mutation in ctDNA was relatively consistent with that in tumor tissue, whether the KRAS mutant allele fraction (MAF) differed was still not reported. So far, the clinical application of ctDNA detection in PC remained inconclusive. Methods: Plasma samples were collected from 110 PC and 52 pancreatic benign (PB) diseases patients. The detection of KRAS mutation in ctDNA was performed using droplet digital PCR and compared with that in matched tumor tissue. We assessed the utility of KRAS MAFs in ctDNA and tissue for pancreatic malignancy assessment. Results: We found that KRAS MAF in ctDNA of PC patients was higher than that of PB patients, and was obviously associated with tumor staging and distant metastasis. However, KRAS MAF in ctDNA was significantly different from that in matched tissue. KRAS MAF in tumor tissue had no significant correlation with the clinical status. In addition, ROC curve analysis revealed that mutant KRAS ctDNA combined with CA19-9 could increase the sensitivity rate of early-stage PC prediction in comparison with CA19-9 test alone. Conclusion: The MAF of KRAS in ctDNA was related to the clinical stage of PC (p = 0.001). Mutant KRAS ctDNA could improve the sensitivity in early diagnosis of PC as a complement to CA19-9. Our study suggested that KRAS mutation in ctDNA could be a valuable circulating biomarker for pancreatic malignancy assessment.